Comparison of colloidal silica involved fouling behavior in three membrane distillation configurations using PTFE membrane. (1st March 2018) - Qin, Wenli; Xie, Zongli; Ng, Derrick; Ye, Ying; Ji, Xiaosheng; Gray, Stephen; Zhang, Jianhua
Abstract: Colloidal silica involved fouling behaviors in direct contact membrane distillation (DCMD), vacuum membrane distillation (VMD) and sweeping gas membrane distillation (SGMD) were studied. Three foulants were used in the experiments, including colloidal silica as representative of particulate foulants, calcium bicarbonate as dissolved inorganic foulant, and NOM (humic acid + alginate + BSA) as the dissolved organic foulant. The three types of fouants were combined to produce four different feed waters: silica alone; silica + calcium bicarbonate; silica + NOM; and silica + calcium bicarbonate + NOM. With 25% feed recovery, it was found that VMD showed the worst performance for most of the foulant combinations due to turbulence dead zones caused by the membrane deformation that increased foulant deposition. For the silica + calcium bicarbonate + NOM feed DCMD had the greatest fouling rate, although DCMD also had the highest flux of all configurations. SGMD showed the best fouling resistance of all configurations, although it was inclined to calcium carbonate fouling because carbon dioxide was removed in the permeate leading to calcium carbonate precipitation and could be alleviated by using air as sweeping gas. For feeds containing high-concentration calcium bicarbonate or carbonate foulants, VMD should be avoided to lower the formation of carbonate precipitants on the membrane surface if scale inhibitors are not used. Graphical abstract: Highlights: Colloidal silica involved fouling behaviors in DCMD, VMD and SGMD were studied. The interaction of inorganic, organics and colloidal silica in membrane fouling was studied. The MD configuration influence on fouling formation was studied. Suitable MD configuration for different foulant containing feed was suggested.